Effects of non-peptide nociceptin/orphanin FQ receptor ligands on methylphenidate-induced hyperactivity in mice: Implications for bipolar disorders. (August 2020) - Asth, Laila; Tiago, Pamella R.F.; Costa, Layse R.F.; Holanda, Victor A.D.; Pacifico, Salvatore; Zaveri, Nurulain T.; Calo', Girolamo; Ruzza, Chiara; Gavioli, Elaine C.
Abstract: Bipolar disorder is a psychiatric pathology characterized by biphasic mood episodes of mania or hypomania and depression. The pharmacotherapy of bipolar disorder has significant adverse effects impairing treatment adherence and patient quality of life. The N/OFQ-NOP receptor system has been widely implicated with mood disorders. Clinical and preclinical findings suggest antidepressants actions for NOP antagonists. More recently, the administration of NOP agonists has shown to promote depressant states. The present study aimed to investigate the effects of non-peptide NOP ligands in methylphenidate-induced manic-like behavior in mice. The NOP agonist Ro 65–6570 (0.01–1 mg/kg, ip), at the higher dose, did not affect spontaneous locomotion per se, but prevented the methylphenidate (10 mg/kg, sc)-induced hyperlocomotion. The NOP partial agonist AT-090 (0.001–0.03 mg/kg, ip) and the NOP antagonist SB-612111 (1–10 mg/kg, ip) did not significantly affect the psychostimulant-induced hyperactivity. Experiments performed with mice lacking the NOP receptor (NOP(−/−)) demonstrated that the treatment with methylphenidate induced similar hyperlocomotion in NOP(−/−) and NOP(+/+) mice. In conclusion, these findings suggest a potential role for NOP agonists in the prevention of manic states, especially by counteracting the hyperactivity symptom of bipolar patients. However, more studies are necessary in order to evaluate these compounds in other features of bipolar disorder. Highlights: The antimanic drug valproate prevented the methylphenidate-induced hypelocomotion. The NOP full agonist Ro 65–6570 at higher doses attenuated methylphenidateinduced hyperlocomotion. The NOP partial agonist AT-090 and the NOP antagonist SB-612111 did not affect manic-like behaviors.